The Bakhti Emirate in Ibn Umar Island, Botan 738 920 AH 1337 1514 AD A new perspective on the founding and preservation of the Kurdish identity of the emirate - Hassan, Prof. Dr. Darwish Youssef (Sulaimani Journal for Humanities, 2025)
This study is divided into two sections. The first section provides a brief overview of the small political entity of the Bakhti Kurds in their initial stronghold, the fortress of Fanak, and then discusses how the Bakhti conquered Ibn Umar Island and established their emirate there.
Keywords: Ibn Omar Island; the Bakhti Kurds; the Mongols; the Haskafi founder